Effects of increasing crystalline lysine and dietary fat on finishing pig growth performance - R G Main; J L Usry; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2003)
A total of 1,024 barrows (each initially 157 lb, PIC L337 x C22) were used in a 28-d study to evaluate the effects of increased crystalline amino acids (none versus 4.5 lb/ton of L-lysine HCl plus L-threonine to maintain the proper ratio relative to lysine) and added dietary fat (none, 3 or 6% choice white grease) on finishing pig growth performance. All experimental diets were formulated with a constant true ileal digestible lysine:ME ratio based on NRC, (1998) ingredient values for ME. A minimum true ileal digestible threonine:lysine ratio of 68% and a minimum true ileal digestible methionine + cystine:lysine ratio of 55% were used in diet formulation. There was no synthetic amino acid by added fat interactions. Increasing added fat increased (linear, P<0.01) ADG and improved F/G. Replacing soybean meal with crystalline amino acids had no affect on growth performance. This indicates that the increased amounts of L-lysine HCl and added L-threonine were used as efficiently as amino acids provided from soybean meal. Neither adding fat nor crystalline lysine affected feed cost/lb of gain using current ingredient prices. However, margin over feed cost (profit) increased as added fat increased because of the increased pig weight due to improved ADG. In summary, these results confirm the improved ADG and F/G when adding fat to finishing pig diets. Furthermore, 4.5 lb/ton of Llysine HCl and L-threonine can effectively replace soybean meal without negatively affecting growth performance of pigs from 157 to 217 lb.; Swine Day, 2003, Kansas State University, Manhattan, KS, 2003
Keywords: Swine day; 2003; Kansas Agricultural Experiment Station contribution; no. 04-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 920; Finishing pigs; Growth performance; Fat; Amino acids; Swine